Liberation Day stories - Saunders, George (New York Penguin, 2022)
lThe ?best short story writer in English? (Time) is back with a masterful collection that explores ideas of power, ethics, and justice, and cuts to the very heart of what it means to live in community with our fellow humans. With his trademark prose--wickedly funny, unsentimental, and perfectly tuned--Saunders continues to challenge and surprise: here is a collection of prismatic, deeply resonant stories that encompass joy and despair, oppression and revolution, bizarre fantasy and brutal reality.
Keywords: Liberation